Respostas

2013-08-21T17:19:49-03:00
x² - 4kx + 1
/\=b²-4.a.c
/\=(4k)²-4.1.1
/\=16k-4
16k-4=0
16k=4
k=16
     4
k=4
2013-08-21T18:05:45-03:00
(k-3) x^{2}-4kx+1=0
Soma das Raizes =  \frac{-b}{a} =  \frac{-(-4k)}{(k-3)}  Produto das Raizes =  \frac{c}{a} =  \frac{1}{(k-3)}
Multiplica cruzado fica:
4 k^{2} - 12k = k-3&#10;&#10;4k^{2} -12k - k +3=0&#10;&#10;4k^{2} - 13k +3 =0[/tex <u>/\</u> = [tex] b^{2} - 4ac
/\ =  (-13)^{2} -4.4.3
/\ = 169-48
/\ = 121
 k_{1} =  \frac{-(-13)+ \sqrt{121} }{2.4}
 k_{1} =  \frac{13+11}{8}
 k_{1} =  \frac{24}{8}
 k_{1} = 3 k_{2} =   \frac{13-11}{8}
 k_{2} = 0,25A melhor resposta seria k_{1} = 3
1 4 1